Financing of research activities of Russian universities from foreign sources - A. Ridiger (Informaciâ i Innovacii)
The volume and sources of co-ﬁnancing by foreign partners of research activities of Russian universities for the period 2010-2020 are analyzed. Identiﬁed funding trends; shows the dynamics of changes in ﬁnancial ﬂows of countries that have made the maximum contribution to the co-ﬁnancing of science of Russian universities.